2010
DOI: 10.4088/jcp.09m05113yel
|View full text |Cite
|
Sign up to set email alerts
|

Assertive Community Treatment as Part of Integrated Care Versus Standard Care

Abstract: clinicaltrials.gov Identifier: NCT01081418.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(39 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…The results are in accordance with previous studies reporting that antipsychotic treatment integrated with several components of psychosocial intervention is superior to traditional medication-alone treatments in terms of dealing with several problems (e.g., psychotic symptoms, social functioning, and compliance to medication) simultaneously in the treatment of schizophrenia [1, 23, 25, 27, 29, 48-50]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results are in accordance with previous studies reporting that antipsychotic treatment integrated with several components of psychosocial intervention is superior to traditional medication-alone treatments in terms of dealing with several problems (e.g., psychotic symptoms, social functioning, and compliance to medication) simultaneously in the treatment of schizophrenia [1, 23, 25, 27, 29, 48-50]. …”
Section: Discussionsupporting
confidence: 82%
“…Patients in the combined-treatment group and their family members received rehabilitation treatments which include 3 modules: medication management, symptom management, and social skill training [25, 27, 35-39]. Each therapy group consisted of 6–8 families.…”
Section: Methodsmentioning
confidence: 99%
“…In Munich, the average length of stay decreased since the implementation of the new integrated care model and patients reported a high level of satisfaction, although the implementation process was not free of difficulties (9). In Hamburg, a new model that focused on severely ill patients (F2x und F3x ICD-10 diagnostic codes) contributed to an increase in the outpatient contacts, a decrease of the average inpatient length of stay, and higher patient satisfaction by maintaining cost-effectiveness (1012). In Krefeld, a new home treatment-based implemented model proved to be effective in increasing the satisfaction of patients and their next of kin, while preserving a constant quality of care when compared to standard inpatient care (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed a reduction in expenses for inpatient treatment with a simultaneous increase in expenses for outpatient treatment and no significant differences in total costs between both programmes were revealed. However, as part of a cost-effectiveness analysis, the authors demonstrated that treatment efficiency (relationship between treatment costs and gain in quality of life) in the ACT group was better than in routine care [9,10]. …”
Section: Introductionmentioning
confidence: 99%